Heritability and correlation estimates of Warner-Bratzler shear force and marbling score from Angus-, Charolais-, Hereford-, and Simmental-sired cattle - Minick, J.A.; Pollak, E.J.; Wilson, D.E.; Dressler, E.W.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The objective of this study was to estimate heritabilities and genetic correlations for Warner- Bratzler shear force and marbling score of longissimus steaks from Angus-, Charolais-, Hereford-, and Simmental-sired cattle in the National Cattlemen’s Beef Association (NCBA) coordinated Carcass Merit Traits Project funded with Beef Checkoff dollars. There were 700 Angus-sired steers, 691 Charolais-sired steers and heifers, 938 Hereford-sired steers, and 1,167 Simmental-sired steers and heifers in the study. Restricted maximum likelihood estimates of the genetic parameters were determined using a sire model with a sire/maternal grandsire relationship matrix. The heritabilities for Warner-Bratzler shear force and marbling score, respectively, were 0.35 and 0.36 for Angus, 0.43 and 0.26 for Charolais, 0.12 and 0.59 for Hereford, and 0.13 and 0.42 for Simmental. The genetic and phenotypic correlations between Warner-Bratzler shear force and marbling score, respectively, were -0.19 and -0.18 for Angus; -0.36 and -0.19 for Charolais; - 0.47 and -0.23 for Hereford; and +0.64 and - 0.11 for Simmental. The high positive genetic correlation between Warner-Bratlzer shear force and marbling score for Simmental sires indicates that as marbling increased Warner- Bratzler shear force increased (decreased tenderness). These results suggest that selection for increased marbling in the Simmental breed would actually have a detrimental effect on tenderness. Selection for Warner-Bratzler hear force in Angus and Charolais could result in improved in tenderness, but little progress would be expected in Hereford sired cattle. In general, selection for marbling score in these breeds would improve tenderness only minimally.
Keywords: Beef; Warner-Bratzler shear force; Marbling score; Angus; Charolais; Hereford; Simmental